2011
DOI: 10.1007/s00418-011-0840-0
|View full text |Cite
|
Sign up to set email alerts
|

Myosin IIB deficiency in embryonic fibroblasts affects regulators and core members of the par polarity complex

Abstract: Wild-type (WT) and myosin heavy chain IIB null [MHCIIB (-/-)] embryonic fibroblasts were used as an experimental model to assess the role of the isoform B of myosin II (MII) in the regulation of the cell shape and intrinsic polarity. Genetic ablation of MHCIIB causes a persistent albeit, unstable protrusive activity in embryonic fibroblasts (Lo et al. in Nonmuscle myosin IIB is involved in the guidance of fibroblast migration. Mol Biol Cell 15:982-989, 2004). Here, we show that MHCIIB-deficient fibroblasts are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 80 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…87 Lgl1 has been reported to associate with both myosin-IIA and myosin-IIB. 88,89 Consistent with Lgl binding to the coiled coil region between ACD1 and ACD2, Lg1 blocks the assembly of myosin-IIA filaments in vitro and regulates myosin-IIA localization in vivo. 89,90 S100A4.…”
Section: Regulation Of Filament Assembly Via Interactions With Regulamentioning
confidence: 89%
“…87 Lgl1 has been reported to associate with both myosin-IIA and myosin-IIB. 88,89 Consistent with Lgl binding to the coiled coil region between ACD1 and ACD2, Lg1 blocks the assembly of myosin-IIA filaments in vitro and regulates myosin-IIA localization in vivo. 89,90 S100A4.…”
Section: Regulation Of Filament Assembly Via Interactions With Regulamentioning
confidence: 89%
“…Isolation of the membrane- and cytosol-enriched subcellular fractions was carried out as previously described [ 10 ; 57 ]. Briefly, cells were washed with PBS containing protein phosphatase and protease inhibitors, collected by scraping, and homogenized to obtain a total cell lysate.…”
Section: Methodsmentioning
confidence: 99%
“…This study also showed that ectopically expressed Lgl1 and NMIIA could be coimmunoprecipitated from cells. However, another study revealed an interaction of Lgl1 only with NMIIB, but not NMIIA, using coimmunoprecipitation of endogenous proteins [44]. This discrepancy remains to be resolved, especially because all charged residues within the proposed Lgl1-binding site of NMIIA are conserved in NMIIB.…”
Section: Regulation Of Nmii Turnover Cyclementioning
confidence: 99%